Intense vibronic modulation of the chiral photoelectron angular distribution generated by photoionization of limonene enantiomers with circularly polarized synchrotron radiation - Fanood, Mohammad M. Rafiee; Ganjitabar, Hassan; Garcia, Gustavo A.; Nahon, Laurent; Turchini, Stefano; Powis, Ivan (Wiley, 2018)
Photoionization of the chiral monoterpene limonene has been investigated using polarized synchrotron radiation between the adiabatic ionization threshold, 8.505 eV, and 23.5 eV. A rich vibrational structure is seen in the threshold photoelectron spectrum and is interpreted using a variety of computational methods. The corresponding photoelectron circular dichroism—measured in the photoelectron angular distribution as a forward-backward asymmetry with respect to the photon direction—was found to be strongly dependent on the vibronic structure appearing in the photoelectron spectra, with the observed asymmetry even switching direction in between the major vibrational peaks. This effect can be ultimately attributed to the sensitivity of this dichroism to small phase shifts between adjacent partial waves of the outgoing photoelectron. These observations have implications for potential applications of this chiroptical technique, where the enantioselective analysis of monoterpene components is of particular interest.